Antihypertensives and melanoma: An updated review. (16th August 2020) - Williams, Natalie M.; Vincent, Louis T.; Rodriguez, Gregor A.; Nouri, Keyvan
Abstract: Antihypertensive medications are commonly prescribed and well‐studied. Given the widespread use and potential side effects, various theories have been made about the relationship between antihypertensives and malignancy, including melanoma. This review describes the current understanding of the most commonly prescribed antihypertensives and their associations with melanoma. The literature demonstrates that diuretics, specifically hydrochlorothiazide and indapamide, may increase the risk of melanoma. While there is no evidence that antihypertensives have a role in melanoma prevention, non‐selective β‐blocker therapy has been associated with a decreased risk of disease progression and recurrence and may also improve outcomes in patients undergoing immunotherapy. In addition, experimental studies reveal that angiotensin‐converting enzyme inhibitors, angiotensin receptor blockers, and calcium channel blockers have anti‐tumor effects, meriting further study.